Mineralogical and geochemical properties and genesis of kaolin and alunite deposits SE of Aksaray (Central Turkey). (January 2021) - Çelik Karakaya, Muazzez; Karakaya, Necati; Temel, Abidin; Yavuz, Fuat
Abstract: The kaolin and alunite deposits, situated approximately 20 km southeast of Aksaray in Central Anatolia, were formed by hydrothermal alteration related to extensional tectonics from the Upper Miocene to Quaternary, mostly from rhyolitic volcanoclastic rocks. The mineralogical and geochemical properties of the deposits were investigated to explain the stages of hydrothermal alteration and the origin of the deposits. X-ray diffraction (XRD), scanning electron microscopy (SEM), and chemical and stable isotope (O, H, and S) studies were carried out on the alteration minerals (e.g., kaolinite, gypsum, alunite, native sulfur and smectite) of the deposits. Kaolinite/halloysite minerals were determined along with mostly alunite- and silica-group minerals (α-quartz, opal-CT, and tridymite), feldspar, native (elemental) sulfur, and partial hematite, goethite, gypsum, cinnabar and realgar. The δ 34 S isotope values for alunite, gypsum and native sulfur are in a fairly narrow range and vary from 5.03 to 6.62‰, 4.5–5.24‰ and 5.97–7.49‰, respectively. The δ 18 O values of the kaolinites and smectites vary from +1.8 to +13.3‰ and from −98 to −152‰, respectively, and their δD values range from −4.2 to 15.7‰ and from −93 to −191‰, respectively, showing a spread that is very close the primitive magmatic water line. From the δ 18 O values, the calculated formation temperatures of the kaolinites and smectites range from 38 to 135 °C and from 29 to 189 °C, respectively. The δ 18 O values of the alunites and amorphous silica vary from 4.4 to 8.9‰ and from −1.1 to 8.4‰, respectively, and the δD values vary from −72 to −87‰, and from −104 to −191‰, respectively. In addition, the formation temperatures of alunite and amorphous silica minerals range from 57 to 100 °C and from 139 to 281 °C, respectively. Hydrothermal alteration progressed in different stages between 29 and 281 °C according to the calculated modal formation temperatures. The isotopic mineral data suggest that the original hydrothermal waters were a mixture of magmatic and meteoric waters. Oxygen and deuterium analyses indicate that kaolinite and alunite formed at lower temperatures than smectite and silica minerals. The determined stable isotopic compositions of the minerals indicate that hydrothermal solutions at different compositions and temperatures played important roles in the formation of minerals. The determined neoformed minerals may have been formed by steam-heated hydrothermal solutions sourced from rhyolitic magma and are mostly of hypogene origin. Highlights: Mineralogical, chemical properties of acid-sulfate hydrothermal alteration. Formation temperature of minerals forming from acid-sulfate hydrothermal alteration. δ 34 S, δ 18 O, and δD composition hypogene, steam-heated originated minerals.